The Learning management using a model based on the STEM Education concept to promote Problem solving and decision-making skills of teacher students - Oonpuy, Wichayaporn (Journal of Inclusive and Innovative Education, 2022)
The purposes of this research were To study the opinions of learning management based on the concept of STEM Education. Experimenting with a learning management model based on the concept of STEM Education Review and analyze the activity process using a model based on the STEM Education concept. To study problem solving skills and decision-making of teachers after the event is organized. And Study the satisfaction of students who receive learning activities based on the STEM Education concept Sample group is a teacher student in Early Childhood Education, Faculty of Education, Phetchabun Rajabhat University. Studied in year 3, room 2, semester 1, academic year 2020, 28 students The statistics used for data analysis were mean, standard deviation. Statistics used in the determination of the t – test Dependent samples. The research results were found that 1. Inquiry on learning management based on the concept of STEM Education and Problem-solving and decision-making skills From the instructor. Mentors and students The respondents had the highest level of opinions on teaching and learning based on STEM Education concept. And saw that it was most important / needed to be promoted Problem-solving and decision-making skills; Seen as important / needed to be promoted at the highest level 2. The results of using the learning management model It was found that after carrying out this activity, students had higher problem-solving and decision-making skills. By design Students use solutions by studying, searching through steps from multiple sources to find solutions. Including being able to solve problems and make successful decisions to discriminate 3. The Results of the review of the activity procedures The researcher has made improvements. To provide clarity in the 7-step retention process and adjust the definition for more clarity. 4. The results of comparing problem-solving and decision-making skills of teachers students. Before learning management The students performed the self-assessment, the results were at a moderate level. After the re-evaluation Have higher self-assessment results Analysis of data from mentors and instructors Found that the assessment results after learning management in educational institutions Have higher overall assessment results 5. The results of the assessment of teachers student satisfaction of the who received the overall learning activities were at the highest level.